2005
DOI: 10.1158/1078-0432.ccr-05-0149
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of the 6-Phosphofructo-2-Kinase/Fructose 2,6-Bisphosphatase/PFKFB3 Family of Glycolytic Regulators in Human Cancer

Abstract: Purpose: Fructose 2,6-bisphosphate (F2,6BP) is a potent activator of phosphofructokinase, which is a rate-limiting enzyme of glycolysis.The concentration of F2,6BP depends on the activity of the bifunctional enzyme, 6-phosphofructo-2-kinase/fructose-2,6-bisphosphatase (PFK-2/ FBPase). Four genes encoding PFK-2/FBPase have been identified and termed PFKFB1 to PFKFB4. PFKFB3 protein is expressed in high levels in human tumors in situ.The purpose of this study was to determine the role of functional interactions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
160
1
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 183 publications
(172 citation statements)
references
References 36 publications
8
160
1
3
Order By: Relevance
“…A representative (of four) gel electro phoresis is shown ine residues, however its significance in the regulation of PFKFB-3 activity via phosphory lation has not been studied yet. There are data that phosphorylation of Ser 490 is responsible for activation of glycolysis in human cancer [18]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A representative (of four) gel electro phoresis is shown ine residues, however its significance in the regulation of PFKFB-3 activity via phosphory lation has not been studied yet. There are data that phosphorylation of Ser 490 is responsible for activation of glycolysis in human cancer [18]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…5, different alternative splice variants of PFKFB3 mRNA have diffe rent quantity and position of serine residues (underlined) in the Cterminus that could have certain significance in regulation of enzymatic activity through serine phosphorylation [11,18]. Moreover, three bigger splice variants of PFKFB3 mRNA (NM_057135, D87241 and D87242) contain an additional exon 13a (29 amino acid segment), which has six ser Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypoxia also induces expression of PFKFB-3 in different mouse organs in vivo, except skeletal muscle [42]. High expression level and phosphorylation status of PFKFB-3 as an important glycolytic regulator was determined in different malignant tumours [43][44][45][46][47]. Because SNARK deficiency contributed to the early phase of tumourigenesis and is important in cancer development and tumour progression [13,14], investigation of the expression of PFKFB-3 and its alternative splice variants, which have different proliferative properties [48], is necessary for understanding the role of SNARK deficiency in tumourigenesis.…”
Section: Protein Kinase Snark and Pfkfb-3 Alternative Splicingmentioning
confidence: 99%
“…3 and 4), supporting the idea that this terminus of the various enzyme isoforms serve to adapt the kinetic properties of the catalytic core to metabolic exigencies of a particular tissue. Alternative splice variants of PFKFB-3 also have different amounts and sequence positions of serine residues which are very important in the regulation of isozyme activity via phosphorylation [39,46]. It was shown that the pattern of alternative splice variants of the PFKFB-3 mRNA differs in different mouse organs (Fig.…”
Section: Protein Kinase Snark and Pfkfb-3 Alternative Splicingmentioning
confidence: 99%